Taking the Lab to the Field: Experimental Tests of Alternative Mechanisms to Procure Multiple Contracts - Anders Lunander; Jan-Eric Nilsson (Fondazione Eni Enrico Mattei (FEEM), 2003)
The first part of the paper reports the results from a sequence of laboratory experiments comparing the bidding behavior for multiple contracts in three different sealed bid auction mechanisms; first-price simultaneous, first-price sequential and first-price combinatorial bidding. The design of the experiment is based on experiences from a public procurement auction of road markings in Sweden. Bidders are asymmetric in their cost functions; some exhibit decreasing average costs of winning more than one contract, whereas other bidders have increasing average cost functions. The combinatorial bidding mechanism is demonstrated to be most efficient. The second part of the paper describes how the lab experiment was followed up by a field test of a combinatorial procurement auction of road markings.
Keywords: D44; L92; 330; Multiple units; non-constant costs; asymmetric redemption values; alternative procurement mechanisms; Auktionstheorie; Öffentlicher Auftrag; Vertrag; Theorie; Schweden